Good and Bad Deaths, or Dying as a Temporal Sequence - Fortin, Sylvie (Anthropologica, 2025)
Based on pre-pandemic research conducted in Montreal among relatives who supported a child, an adult, or a senior through illness and end of life, this paper discusses the time of dying as a temporal sequence. Identified as the (long) time of illness, the time of end of life (the hours or days preceding death) and the time of death, each time in this temporal sequence had a bearing on whether a death was perceived as good or bad by the over 100 relatives we met with. The end-of-life trajectories we documented bring into question the elements that contribute to the many-sided notions of good or bad deaths as they intersect without offering unambiguous points of reference. When people refer to a bad death, are they referring to the time of illness, the time of end of life, or the time of death? The imbalance between these different times or, on the contrary, their concordance gives rise to the perceptions of a bad death or a good death that are at the heart of the “dying with dignity” discourse.